An exercise prescription for patients with lung cancer improves the quality of life, depression, and anxiety - Lei, Juntian; Yang, Jianyu; Dong, Lei; Xu, Jilai; Chen, Jing; Hou, Xiao; Bai, Zhenmin (Frontiers in Public Health, 2022)
Introduction: Lung cancer has the highest morbidity and mortality among all cancers. Patients with lung cancer inevitably confront psychosocial discomforts and progressively experience depression and anxiety that potentially impact the clinical outcomes (e.g., quality of life (QoL)). These mental disorders in lung cancer may effectively be alleviated with prescribed Chinese traditional mind-body exercise. This study aims to determine the effect of the exercise prescription containing Chinese traditional mind-body exercise on the QoL, depression, and anxiety in patients with lung cancer. Methods: 52 non-small cell lung cancer (NSCLC) patients recruited from China-Japan Friendship Hospital were divided into the experimental group (N = 26) and the control group (N = 26). The experimental group was treated with an 8-week exercise prescription containing aerobic and resistance training. The control group received usual care during the study period. The QoL, depression, and anxiety were separately investigated using EORTC QLQ-C30, EORTC QLQ-LC13, Self-rating Depression Scale (SDS), and Self-rating Anxiety Scale (SAS) at the baseline and post-intervention. The scores of questionnaires were analyzed using the paired sample and independent sample t-test to explore the intra- and inter-group differences respectively. Results: The EORTC QLQ-C30 scores of physical functioning, role functioning, emotional functioning, and global QoL in the experimental group at the post-intervention were significantly higher than those at the baseline. The EORTC QLQ-C30 scores of fatigue, pain, dyspnea, and insomnia in the experimental group at the post-intervention were significantly lower than those at the baseline. The SDS scores (baseline: 57.74 ± 8.77 vs. post-intervention: 51.42 ± 7.31, p < 0.05) and SAS scores (baseline: 56.63 ± 9.39 vs. post-intervention: 49.16 ± 7.83, p < 0.05) in the experimental group at the post-intervention were significantly lower than those at the baseline. Conclusions: The 8-week exercise prescription containing moderate-intensity Baduanjin (5 days per week) can effectively alleviate the QoL, depression, and anxiety in patients with NSCLC. Our exercise prescription is an effective supportive treatment for lung cancer patients with depression and anxiety.